The Rats Woke Up – On Figures of Dissent in Belgrade’s Underbelly in Pavlović’s Vision - Nikica Gilić ([sic])
The characters of Živojin Pavlović’s seminal film The Rats Woke Up (Buđenje Pacova, 1967), regularly discussed in the context of the Yugoslav Black Wave cinema, offer significant and very intriguing figures of dissent. The film depicts misfits, bottom-dwellers, and dissidents living on the margins of society in the largest and capital city of Belgrade at a time when Black Wave authors have been breaking some new grounds for Yugoslav cinema and influencing artists well after the movement became a part of history. This essay concentrates on the characters and their interaction, the complexity of which suggests the complexity of Pavlović’s criticism of everyday life and institutions in the 1960s Yugoslavia.Keywords: Živojin Pavlović, The Rats Woke Up, Black Wave, Belgrade, figures of dissent, film criticism, Yugoslav cinemaHistorical studies of socialist Yugoslav cinema often place special emphasis on the Black Wave tendency of the 1960s and early 1970s (Goulding), sometimes even considering it to be a proper movement. Owing to the Black Wave cinema’s international success accompanied by film reviews and scholarly studies, as well as several major festival awards, it is deemed as one of the lasting cultural legacies of socialist Yugoslavia, a country dissolved at the beginning of the 1990s. The importance of cinema in Yugoslavia’s popular culture is extensively discussed in Radina Vučetić’s book Koka-kola socijalizam (Coca-cola socialism), albeit often from the perspective of western influences, while Greg DeCuire Jr. (2013) discusses the role of “realist” depictions of war and partisan fight in Yugoslav cinema as a part of the State-Building process, building the consensus around the Yugoslav values. The role of the Black cinema, however, points to the complexity of the cinematic institution, wide enough to embrace imported films, local cinematic populism, and (at least for a length of time) the Black Wave cinema (Vučetić 142-66).